(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
Before studying the tectonomagnetic effect, the magnetoelastic effect of rocks was studied under laboratory and field conditions. The results showed that reversible and irreversible changes are manifested in the remanent magnetization. Until now, the detected changes have manifested themselves in the tectonomagnetic field in the form of reversible changes. The absence of irreversible changes suggests that physical processes are not fully reflected in the tectonomagnetic field. In 2021, at the geomagnetic station irreversible changes were observed in the tectonomagnetic field, which was a consequence of the foci located 20 km from the "Saragyugh" Geomagnetic Station. The observed reversible and irreversible changes fully reflect the process of elastic and plastic deformations occurring in the sources of nearby earthquakes.